No need to renew: The end of Japan’s teacher license renewal system and the future - Chapple , Julian (Asian Journal of Education and Training, 2023)
In 2007, the Japanese Ministry of Education revised the Education Law to pave the way for the introduction of a teaching license renewal system in 2009. The reform required all teachers to complete at least 30 hours of training in specially tailored university courses as a prerequisite for renewal of their teaching licenses every 10 years. In late 2021, however, the government abruptly announced it was ending the scheme in 2022 in a policy about face reminiscent of the abolition of yutori kyōiku (“education without pressure”) in 2007. This qualitative study aims to examine the background, outline and issues of Japan’s license renewal system in order to understand the reasons for its demise and illustrate the similarities with the yutori kyōiku experiment. Drawing on interview data and reflections from the author’s experiences with the system over 12 years, it looks at some of Japan’s unique training opportunities and, employing examples from other countries, examines what kind of ‘training’ is needed moving forward. It concludes by calling for a widening of the interpretation of ‘training,’ and indeed, the license itself, so as to increase diversity in what is a considerably restrictive employment sector.